The Impact Of Islamic Work Motivation On The Connection Between Employee Performance And Religiosity - Maulana Mukti Khadafi; Itang Itang; Erdi Rujikartawi; Efi Syarifudin (FEB Universitas Sultan Ageng Tirtayasa, 2025)
Islamic work motivation as a mediating component in the relationship between employee performance and religiosity. Using Islamic work motivation as an intervening variable, this study attempts to ascertain if religiosity has an impact on employee performance at the Bank Muamalat Serang Branch Office. The study's variables include employee performance as the dependent variable, Islamic work motivation as the intervening variable, and religion as the independent variable. Descriptive and causal research are two quantitative methodologies used in this study. The Structural Equation Model (SEM) in SmartPLS Software version 3.2.9 was used to evaluate data from the three variables. In this study, the sample used was a saturated sample, namely the total number of employees, amounting to 33 respondents. Based on the results of data analysis, it shows that religiosity has a negative and insignificant effect on employee performance, Islamic work motivation has a positive and significant effect on employee performance, religiosity has a positive and significant effect on Islamic work motivation, and Islamic work motivation is able to mediate the relationship between religiosity and employee performance at Bank Muamalat Serang Branch Office.